Isolated fetal lymphatic malformation of the thigh: prenatal diagnosis and follow-up - Huseyin Durukan; İlay Gözükara; Murside Cevikoglu; Talat Umut Kutlu Dilek (University of São Paulo, 2017)
Fetal lymphatic malformation can be found in different parts of the fetal body. It occurs most frequently in the nuchal and axillary region and less frequently in the abdomen or inguinal areas. Lymphatic malformation has been associated with fetal aneuploidy, hydrops fetalis, structural malformations, and intrauterine fetal death. A 31-year-old gravida 3, para 2 woman was admitted to our hospital at 22 weeks of gestation (confirmed by ultrasonographic examination). The fetus was alive, and had a mass derived from the left inguinal region extending to the anterior left leg with fluid-filled cavities about 3-5 cm in size. There was no evidence of intra-abdominal extension of the mass. Amniocentesis was performed. Fetal magnetic resonance imaging revealed a left inguinal cystic mass, which extended to the left thigh. Antenatal follow-up was uneventful. The mother gave birth at term with a cesarean section. Postnatal clinical examination and imaging examination confirmed the diagnosis of lymphatic malformation. Fetal lymphatic malformation carries a high risk of aneuploidy and fetal malformations. Patients diagnosed with lymphatic malformation in antenatal follow-up should be assessed in terms of coexistent anomalies. Fetal karyotyping should be done and the fetus should be monitored for fetal hydrops